Knowledge, awareness and practice of epilepsy among caregivers in pediatric wards at Hospital USM - Muhamad, Nurul Asyikin (2020)
Epilepsy is a most common neurological disease among children. Epilepsy is still a highly misunderstood disease that can cause misconception and social misunderstanding. The aim of this study was to assess the knowledge, awareness and practices ofepilepsy. A cross sectional descriptive design was used for this study. A sample of 62 cafegivers at pediatric wards was taken by using simple random sampling method. Instrument used for this study was set of questioner compose of demographic data, caregiver’s knowledge, awareness and practices ofepilepsy. Scoring was based on dichotomous questions. For each correct answer one point will be assigned. Data was analyzed on SPSS (version 24) and results were presented in tables. The findings revealed that more than half (62.9%) had a satisfactory knowledge, 33.9% had a good knowledge and 3.2% had a ppor knowledge of epilepsy. Other than that majority 45.2% of the respondents had a moderate awareness, 29% had a good awareness and 25.8% had a poor awareness. Moreover, 80.6% had a good practice, 17.8% had a moderate practice and 1.6% had a poor practice.There was significant linear relationship between level of knowledge of epilespsy with level of practice of epilepsy among caregivers in pediatric wards at Hospital USM.p value = 0.031 (<0.05), thus reject null hypothesis. r = 0.274, the relationship is weak and positive. In conclusion, the study findings showed a requirement for adequate information, well-organized epilepsy programs and proper practice of epilepsy among caregivers for reduction epilepsy disease in Malays